THEORETICAL AND METHODOLOGICAL ANALYSIS OF CONCEPTS MODERNIZATIONS AND SUBSTRATE REFORM TEACHER PROFESSIONAL TRAINING IN MODERN SOCIETY (Pedagogy of Higher and Secondary Education, 2022)
The article deals with certain educational problems of nowadayscommuniti: the mice of illiterate, the expulsion of pupils from schools, inadéquate level graduates.